Probing the Thermal Stability and Microstructural-Mechanical Behaviour of Laser-Welded 17-4 PH Stainless Steel - B. Kumar; A.K. Sahu; D. Das; S. Bag (Archives of Metallurgy and Materials)
Dissimilar-weld-fabrications are created to capture privilege of certain attributes of each component to enhance the potential of overall structure. Induced residual stress owing to non-uniform thermal cycle, strain developed by virtue of metallurgicaltransformation, and dramatic difference in thermo-physical and thermo-mechanical property, proved to be a major drawback and limits application certainly. Present study includes amalgamation of material-characterization and numerical-modelling to overcome aforementioned issue. The 17-4 precipitation-hardened steel was joined with SS316 steel by CO2 laser-welding technique using different-heat-input. It is noticed that the distribution and amount of δ-ferrite controls the on-site behavior relating to thermal stability, microstructural characteristics and residual stress generation. This work is attempted to understand thermal behavior as well as its correlation with δ-ferrite formation and residual stress distribution. Sequential-coupled-thermo-mechanical model proposed to developed for dissimilar weld joints at different process conditions. Finally, the interrelation between microstructure and the typical pattern of residual stress believed to be investigated systematically.